THE EFFECT OF LEARNING MOTIVATION THROUGH STUDENTS’ READING ABILITY ON ENGLISH LEARNING ACHIEVEMENTS - Ida Maulida, (Journal of Innovation Research and Knowledge, 2025)
This study aimed to examine the effect of learning motivation and students' reading ability on English learning achievements. The research employed a survey method with correlational and regression analysis to investigate the relationship among the variables. The participants were second semester students of the English Education Study Program at Universitas Subang. Data collected through classroom observations, interviews, and students' tests. The findings revealed that learning motivation and reading ability simultaneously had a significant effect on students' English learning achievements (F = 55.024, Sig. = 0.000). The regression model showed a strong relationship (R = 0.812) and explained 65.9% of the variance in English achievement (R² = 0.659). Partially, learning motivation (β = 0.378, t = 5.161, Sig. = 0.000) contributed more strongly (Beta = 0.520) compared to reading ability (β = 0.307, t = 3.697, Sig. = 0.000; Beta = 0.373). These results indicate that students with higher learning motivation and better reading ability tended to achieve better outcomes in English learning. The study concludes that learning motivation plays a more dominant role than reading ability in improving English learning achievements. It suggests that teachers should foster students' motivation alongside reading strategies to enhance their academic success in English.